2017
DOI: 10.1111/josh.12524
|View full text |Cite
|
Sign up to set email alerts
|

Educational Outcomes Associated With School Behavioral Health Interventions: A Review of the Literature

Abstract: Our findings are consistent with reports documenting health benefits of school behavioral health frameworks and programs and can facilitate further efforts to support school behavioral health for a range of stakeholders interested in the benefits of school behavioral health programs and frameworks on academic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 74 publications
1
13
0
1
Order By: Relevance
“…The student outcomes of the current study are also consistent with those observed in other recent comprehensive school‐based MH programs targeting demographically similar students . Even relatively modest improvements such as demonstrated in these studies, when extrapolated to large populations, have the potential for a significant public health and educational impact …”
Section: Discussionsupporting
confidence: 86%
“…The student outcomes of the current study are also consistent with those observed in other recent comprehensive school‐based MH programs targeting demographically similar students . Even relatively modest improvements such as demonstrated in these studies, when extrapolated to large populations, have the potential for a significant public health and educational impact …”
Section: Discussionsupporting
confidence: 86%
“…The results of this study provides an argument for school managements and teachers to integrate EOtC as a regular part of the academic teaching in primary schools in order to promote psychosocial well-being, an important aspect of pupil's mental health. 1 In comparison to other universal schoolbased health initiatives integrated into academic curricular teaching, 9,10 EOtC has the advantage that it has minimal interference with delivery of the core curriculum. Several initiatives should be taken to promote pupils' psychosocial well-being using EOtC.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…EOtC often includes activities described as child‐led, hands‐on problem solving and experimentation, peer collaboration, and inductive learning approaches, as well as physical activity, games, and play . Although EOtC can be regarded as a school‐based health initiative integrated into academic curricular teaching, EOtC is distinguished by not involving explicit health education.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…School health services, as a symbol of the implementation of health policies in the educational system, are of great importance for the following reasons: Attention to human capital as a guarantee of community development (20), health education (2), mental health and well-being of individuals (21), the role of school health behavior in school outcomes (22), importance of student engagement and safety (23), changing expectations and perceptions of the school (24), education and health development (25), and there are many challenges for providing school-based health services to school children for a variety of reasons. In Iran, about 16% of the total population are students and paying attention to their health issues and the provision of appropriate health services is a difficult position.…”
Section: Introductionmentioning
confidence: 99%